Factors influencing moderate‐to‐vigorous intensity physical activity across different living arrangements in older adults - Ando, Suguru; Yamashina, Yoshihiro; Iwamura, Masaki; Yamato, Yosuke; Morita, Emiko; Nanikawa, Wataru; Kikuchi, Yui; Kumabe, Sho (Health Promotion & Physical Activity, 2025)
Purpose: This study aimed to investigate the factors associated with moderate-to-vigorous physical activity (MVPA) in older adults, comparing those living in care facilities with community-dwelling individuals. Additionally, it examined diurnal variations in physical activity across different intensity levels. Materials and Methods: This cross-sectional study included 10 older adults residing in a care facility (mean age 84.0 ± 6.2 years) and 17 community-dwelling older adults (mean age 75.7 ± 4.7 years). Participants wore a triaxial accelerometer for 1 week to measure sedentary behavior (SB), light physical activity (LPA), and MVPA. Data were analyzed by dividing the 15-h period (6:00–21:00) into five 3-h intervals to examine activity patterns. Descriptive statistics, independent t-tests, and multiple regression analyses identified factors associated with MVPA. Results: Compared with community-dwelling older adults, their counterparts in care facilities engaged in significantly less MVPA. Long-term care certification, daily step counts, and time spent in LPA were key factors associated with MVPA. Diurnal patterns revealed that community-dwelling older adults were more active from 9:00–18:00, whereas those in care facilities spent more time in SB, particularly between 9:00 and 12:00. Conclusions: Long-term care certification, daily step counts, and LPA were key factors influencing MVPA. Furthermore, significant differences in physical activity patterns between institutionalized and community-dwelling older adults highlight the need for tailored activity promotion programs.